Plio-Pleistocene deep-sea crinoid (Echinodermata) diversity from the western Rodrigues Ridge, Indian Ocean, revealed by microfossil evidence - Roux, Michel; Thuy, Ben; Gale, Andy S. (Zootaxa, 2025)
The deep-sea crinoid fauna of the Indian Ocean is still only partially known and its relationships with the Atlantic and W Pacific faunas remain questionable. Isolated ossicles, more or less biocorroded, of six species belonging to five families of stalked crinoids and one of comatulids were found in a sediment of late Pliocene to early Pleistocene age collected at a depth of 1460 m on the western Rodrigues Ridge. The material described contains three species of stalked crinoids including two new species of Rhizocrinidae. Paraconocrinus, a common genus in the Eocene, was previously unknown beyond the early Miocene. Cherbonniericrinus and Porphyrocrinus have representatives in the present-day oceans, the former only in the NE Atlantic, the latter in the Atlantic and Indo-western Pacific. The ossicles of Porphyrocrinus have been attributed to the extant species P. polyarthra known from the southwestern Indian Ocean, and have allowed us to improve the species diagnosis. P. polyarthra presents close affinities with two Atlantic species. The apparently high diversity of this Plio-Pleistocene fauna is due to a mixture of ossicles from autochthonous mesobathyal species and allochthonous epibathyal ones that lived at shallower depths.